Between traditions: Stephen Ball and the critical sociology of education. (1st November 2013) - Apple, Michael
Stephen Ball's work has deservedly received a good deal of attention. In this article, I detail a number of tasks in which the critical sociologist of education – as a 'public intellectual' – should engage. I then place Ball's work within these tasks and evaluate his contributions to them. In the process, I show that one of the things that set Stephen Ball apart from many others is his insistence that both structural and poststructural theories and analyses are necessary for 'bearing witness' and for an adequate critical understanding of educational realities. I demonstrate how he creatively employs both sets of traditions. At the same time as I am very positive in my evaluation of his contributions, I suggest a number of issues that Ball and those who are rightly influenced by his work could productively deal with to go further into the complexities of the relationship between education and the politics of redistribution and recognition.